Peta Persebaran Rumah Layak Dan Tidak Layak Huni Di Kabupaten Kendal - Vivi Ferliana Putri; Bambang Agus Herlambang (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
At this time, the government is very aggressive in implementing programs to reduce poverty in this country. One of the programs currently running is Self-Help housing stimulant assistance (BSPS) or commonly known as house renovation. To encourage and increase self-sufficiency in improving the quality of houses and building new houses, along with infrastructure, facilities and public utilities (PUPR Ministerial Regulation Number 07/PRT/M/2018). However, the implementation of this assistance program currently still uses conventional methods in collecting data, one of which is data on uninhabitable houses. Every country has a responsibility to fulfill the needs and rights of its citizens to adequate housing, either directly or indirectly. The current condition in Kendal Regency is that ownership of livable houses is still not affordable for some people, this is clearly seen by the existence of slum settlements even in big city areas. There are still many residents who do not have access to their rights to livable housing due to financial limitations. At the requirements engineering stage, the waterfall model is used with the application of a geographic information system. The results of system testing show that the system runs properly according to design.